Students’ Strategies Used for Idiom Translation at SMA Swasta Pencawan Medan - Stevani Lika Sari Tarigan; Marta Rejeki Manalu; Ayu Supriani Tampubolon; Yenita Br Sembiring (Linguistic, English Education and Art (LEEA) Journal, 2020)
The research aims to find out the student's strategies in translating idioms. The method used in this study qualitative descriptive, this study was conducted at SMA SwastaPencawan Medan with the samples were 23 students of XI-MIA-2. The researcher used an essay test with 25 questions to translate idioms sentences. The result collection collected data from the students convert sentence researchers provided the database on the results of students' strategies in translating idioms on an essay test. Using a phrase of similar meaning in form result show there were 61 (34,27%), using a language of same meaning but dissimilar form in form show there were 19 (10,67%), translating by paraphrase in form result show there were 70 (39,33%) and translation by omission in form show there were 28 (15,73%). The result showed that many students translate idioms sentences with translation by paraphrase. The dominant strategies students are predominantly translation by paraphrase, and most students cannot turn the idiom in to the sentence that has been given. Keywords: strategies, translation idiom sentences, senior high school